Giant subcutaneous granuloma annulare - M R Harish; B M Shashikumar; Priyanka R Magod; Deepadarshan K Gowda (Wolters Kluwer Medknow Publications, 2021)
Subcutaneous granuloma annulare is an uncommon, benign self-limiting cutaneous disease, almost exclusively seen in young children. We report a case of 31-year-old male patient, presented with asymptomatic firm plaques over the left lateral malleoli and dorsum of the feet. Histopathological examination was done to confirm the diagnosis and the lesions responded well to monthly doses of the combination of rifampicin, ofloxacin, minocycline (ROM) therapy and intralesional steroid therapy. This case is reported for its unusual presentation of very large plaque in an adult male and its resolution after combined ROM and intralesional steroid therapy.